ESPELHO, ESPELHO MEU, QUEM É MAIS IMPORTANTE DO QUE EU? UM ESTUDO EXPERIMENTAL SOBRE O PAPEL DO PREÇO NO MERCADO DE COSMÉTICOS - Silva, Bruno Rodrigues (2008)
In a context where transformation and change are always present in the business environment, researches executed by private companies point to the disparity of sales increase and the decrease value for cosmetics products. To check this, an experimental study with 225 people was performed to measure the relation between price perception and purchase intention. Representing the largest Sales volume for products in the industry, the shampoo was the item chosen for the experimental scenario created in the study. The proposal was, through a regression model, verify the relationship between price perception with purchase intention, considering that some variables may interfere in this relation. Due to their presence in the marketing theory, degree of involvement, education and income were choosen. Validation procedures for the sample and variables were performed. To ensure that the alleged pré-made were not broken, the analysis of residues found was performed, confirming the homogeneity in the results. The initial association between price perception and purchase intention in the proposed model corroborated with the finding of existing studies. For the other variables, only the dimensions of perceived value and well being associated to the level of involvement, achieved statistically significant results that justify accepting the proposed association. The results were credited to the mixture of utilitarian and hedonistic character that the product has. As a highlight to business managers in the sector the hedonic element appears as the Best path to the companies seeking positioning and trying to diferentiate their product.